Changes in the Pharmacokinetics and Pharmacodynamics of Sildenafil in Cigarette and Cannabis Smokers - Mohammed Murtadha; Mohamed Ahmed Raslan; Sarah Farid Fahmy; Nagwa Ali Sabri (MDPI AG, 2021)
Sildenafil citrate, a widely-used oral therapy for erectile dysfunction, is a cytochrome P3A4 (CYP3A4) enzyme substrate. Studies have reported that this substrate has an inhibitory effect on CYP3A4 enzymes in long-term cigarette and cannabis smokers, which predominantly mediate the hepatic elimination of sildenafil. Cigarette and/or cannabis smoking could therefore alter the exposure of sildenafil. The aim of this study was to examine the effect of smoking cigarettes and/or cannabis on the pharmacokinetics, pharmacodynamics, safety and tolerability of sildenafil. Thirty-six healthy human subjects were equally divided into three groups: non-smokers, cigarette smokers and cannabis smokers. Each group was administered a single dose of sildenafil (50 mg tablets). The primary outcome measures included the maximum concentration of sildenafil in plasma (Cmax), the elimination half-life (t1/2) and the area under the plasma concentration time curve from zero to time (AUC0-t). The pharmacodynamics were assessed by the International Index of Erectile Function (IIEF-5). The exposure of sildenafil (AUC0-t) showed a statistically significant increase in cigarette smokers (1156 ± 542 ng·h/mL) of 61% (p < 0.05) while in cannabis smokers (967 ± 262 ng·h/mL), a non-significant increase in AUC0-t of 35% (p > 0.05) was observed relative to non-smokers (717 ± 311 ng·h/mL). Moreover, the Cmax of sildenafil increased by 63% (p < 0.05) and 22% (p > 0.05) in cigarette smokers and cannabis smokers, respectively. Cigarette smoking increases the exposure of sildenafil to a statistically significant level with no effect on its pharmacodynamics, safety and tolerability.